8-Year-Old Child with Cerebral Palsy Treated with Pelvic Osteotomies Using 3.5 mm Blade Plate Having Subsequent Bilateral Implant Aseptic Loosening: A Case Report - Ahmed Nahian; Julieanne P. Sees (University Library System, University of Pittsburgh, 2021)
Background: Cerebral palsy (CP) is a central problem of the brain due to neurological insult that affects muscle posture, tone, and movement, resulting in poor motor control and dysfunctional muscle balance affecting hip joints in the growing child. Surgical treatment of hip and, if present, acetabular dysplasia addresses the femoral neck-shaft angle, appropriate muscle lengthening, and deficiency of acetabular coverage, as necessary. The surgeons perform proximal femoral osteotomies (PFOs) mostly with fixed angled blade plates (ABP) with proven success. The technique using an ABP is common and requires detailed attention to perform and to teach.  The case: In this case, an eight-year-old ambulatory patient with CP underwent bilateral proximal varus femoral derotational and pelvic osteotomies for the neuromuscular hip condition with a 3.5 mm Locking Cannulated Blade System (OP-LCP) by OrthoPediatrics Corp instead of the use of the conventional 4.5 mm ABP procedure, resulting in aseptic loosening. Conclusion: Due to the child's underdeveloped posture, the surgeon utilized the 3.5 mm instrumentation for a child-size implant, which worked sufficiently for the surgery but may not have loosened if a similar child-size blade plate system of 4.5 mm screws was implanted. While the ABP and OP-LCP systems are effective and safe for internal corrections of PFOs, the OP-LCP system may aid the residents in learning the procedure with higher confidence, fewer technical inaccuracies, and refined outcomes. Both systems are safer and viable for the treatment of neuromuscular hip conditions.